2015
DOI: 10.1095/biolreprod.114.124008
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase Activity and Telomere Length in Male Germ Cells

Abstract: Telomeres are located at the outermost ends of all eukaryotic chromosomes and provide for the maintenance of genomic stability and integrity during the life span of organisms. The length of telomeres shortens due to each round of DNA replication, genotoxic insults, and/or reactive oxygen species. To counteract this shortening, certain types of cells, including stem cells, male/female germline cells, granulosa cells, early embryos, and most cancerous cells, express an enzyme known as telomerase, which has the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 110 publications
3
49
0
Order By: Relevance
“…After adjustment for covariates and random effect of tissue type, RTL showed a positive association with increasing quartiles of TERT expression (p=0.005 including testis and p=0.002 excluding testis) and of DKC1 expression (p=0.001 including testis and p=3x10 -4 excluding testis) across all tissues. Overall these results support the following: (1) high telomerase activity in testis (i.e., spermatocytes) likely contributes to longer TL observed in that tissue and (2) GTEx tissue samples consist primarily of differentiated cells, which typically have little to no telomerase activity, resulting in minimal detectable association between telomerase activity in those cells and the observed TL (32,33).…”
Section: Tl Is Associated With Telomerase Subunit Expression Across Tsupporting
confidence: 72%
See 1 more Smart Citation
“…After adjustment for covariates and random effect of tissue type, RTL showed a positive association with increasing quartiles of TERT expression (p=0.005 including testis and p=0.002 excluding testis) and of DKC1 expression (p=0.001 including testis and p=3x10 -4 excluding testis) across all tissues. Overall these results support the following: (1) high telomerase activity in testis (i.e., spermatocytes) likely contributes to longer TL observed in that tissue and (2) GTEx tissue samples consist primarily of differentiated cells, which typically have little to no telomerase activity, resulting in minimal detectable association between telomerase activity in those cells and the observed TL (32,33).…”
Section: Tl Is Associated With Telomerase Subunit Expression Across Tsupporting
confidence: 72%
“…TERT and TERC expression were low or undetectable in most tissues and were not associated with TL within any tissue, likely because progenitor cells, which express telomerase, are not present in large numbers in adult tissues, which consist primarily of differentiated cells. Notably, testicular TL was ~1.5-2.5-fold longer than TL in any other tissue type, and TERT was expressed in 100% of these samples and at higher levels than any other tissue, consistent with predominance of spermatogenic cells in testis (i.e., cells developing from germ cells into spermatozoa) which have high telomerase activity (33).…”
Section: Discussionmentioning
confidence: 64%
“…Considering the role of telomeres in meiosis and maintenance of genome integrity, the telomere shortening might lead to impaired spermatogenesis, followed by germ cells death. In fact, the increased expression of telomerase in testis in primary spermatocytes is consistent with its role in meiosis I [37] . Many factors have been known to be involved in male infertility through spermatogenic impairment.…”
Section: Discussionsupporting
confidence: 54%
“…Some authors suggest a selection of a subset of sperm cells with longer telomeres, or increased telomerase activity in spermatogonial stem cells in aged men (Kalmbach et al, 2013). Other hypotheses propose reduced telomere erosion due to reduced proliferation of spermatogonia in elderly men (Ozturk, 2015), epigenetic processes in male germline stem cells during ageing (Blasco, 2007) or a more active ALT mechanism in spermatogenic cells in aged men (Bryan, Englezou, Gupta, Bacchetti, & Reddel, 1995;Jorgensen, Fedder, Koelvraa, & Graakjaer, 2013;Ozturk, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, TL steadily increases in spermatogenesis stages (Ozturk, 2015). Further, it has been reported that sperms from older men have longer telomeres than sperm from young men (Baird et al, 2006;D.…”
Section: Introductionmentioning
confidence: 92%